The acquisition of Sprouts Farmers Market, Inc. by Kroger Co. - Coelho, Tiago Jorge Pinto Teixeira (2020)
This dissertation aims to explore the eventual acquisition of Sprouts Farmers Market by Kroger Co. The food and grocery retail sector is under a profound and disruptive transformation process. The entrance of international hard discounters and behemoth online retailers, the consumer’s less propensity to cook and convenience-driven preferences, and the usage of data-intensive technologies shook the industry’s future prospects. Brick-and-mortar retailers, with their profit margins crushed and stagnant growth possibilities, crave for new sources of income. As a result, M&A activity emerges as a reliable option, with Sprouts on the frontline as the optimal target. Kroger and Sprouts’ intrinsic value equals 35,459 and 3,484 million USD, respectively. The transaction will be based on a friendly, all-cash approach, with a 30% premium over Sprouts’ share price on July 15. The deal will be financed using Kroger’s cash reserves, proceeds from the sale of assets and through the issuance of debt. It is expected that the acquisition would yield 1,141 million USD in synergy value, where 420 million USD would be captured by Kroger’s shareholders.